Crystal Orientation and Dislocation Slip - Malcolm Griffiths (Metals, 2023)
It is a widely held belief that dislocation slip has a direct effect on crystal orientation. Some of the confusion may be attributed to semantics when researchers are referring to related effects of dislocations on crystal orientation; either elastic bending due to constraints or the creation of geometrically necessary dislocations by climb. This communication highlights the distinction between the two and discusses why what is often imagined conflicts with what is real and possible. It is demonstrated that deformation-induced changes in the orientation of crystals are primarily limited to twinning and collections of geometrically necessary dislocations (GNDs), which in the most extreme cases are sub-grain boundaries. Alternate explanations for texture changes related to dislocation slip are provided, and they challenge the notion that grains can simply rotate because of dislocation slip through some undefined mechanism.